Psychometric properties of the Iranian version of Birth Satisfaction Scale-Revised - Nasiri, Saeideh (J Res Med Sci, 2020)
BACKGROUND: The precise measurement of childbirth satisfaction demands a reliable tool specifically designed for maternal care and birth satisfaction. It was designed to measure the degree of women's satisfaction with childbirth. The purpose of the present study was to translate and analyze the psychometric properties of the Birth Satisfaction Scale-Revised (BSS-R) in Iranian women. MATERIALS AND METHODS: This is a methodological cross-sectional study. Five health centers in various regions of Kashan were affiliated to Kashan University of Medical Sciences, Kashan, Iran. Two hundred and twelve mothers who were referred to the health centers and had childbirth during the last year were included. The face and content validity were obtained after backward–forward translation of the Iranian version of BSS-R by 12 faculty board members in midwifery and reproductive health fields. The construct validity of the tool was determined using confirmatory factor analysis on 212 women in the postpartum period. The internal consistency and reliability of the tool was evaluated by Cronbach's alpha coefficient and intraclass correlation coefficient (ICC). The collected data were analyzed in SPSS (version 16.0) and EQS 6.1. RESULTS: The result of face and content validity was minor modifications in some words. Confirmatory analysis results indicated that there was an acceptable fit with a three-factor model. Cronbach's alpha was estimated for the whole tool 0.74, and the alpha of the three subscales ranged from 0.698 to 0.801. ICC for determining reliability was 0.77. CONCLUSION: The Iranian version of BSS-R was a reliable and valid tool for assessing the women's satisfaction with their childbirth care.